Práticas do psicólogo em instituições públicas de saúde: o cuidado para com outro. - Carvalho, Liliane Brandão (2006)
The psychologist takes up the challenge of fitting into the public health services, more precisely into the general non-psychiatric institutions characterized as an specific locus of practice and comprehension of the issues related to the continuum health-illness. However, acting on the complex field of collective health imposes to this professional a review of his/her practice, a questioning of the traditional presuppositions and, above all, an ethical discussion that leads to another attitude regarding the user of the service. Caring assumes the configuration of this attitude of respect and embracement of the other’s suffering, whose way does not follow reason any longer, nor the path of knowledge-power, but the affection and the ethical listening. The aim of this study is to understand the meanings attributed by the psychologist to the care for the other in his/her practice in the public health institution in Fortaleza. Having an exploratory character, this study is qualitative, in a critical-interpretative perspective of phenomenological basis, and adopts as methodological underpinning the philosophical hermeneutics. The subjects were eight women-psychologists who are part of the personnel of the public health network. The instrument employed was the non-directive interview, as it facilitates the dialogue and the free expression of the subjects’ daily living. The in-depth analysis of the accounts of each subject evidenced three central thematic axes: the insertion in the field of public health; the psychologist’s practice: knowing and doing at play; and conceptions on the ethical dimension of care. Issues related to the academic background, considered flawed in what regards the discussion about health as a collective dimension, to the lack of previous experience in the field of health, to the very process of professionalization and to the precarious working conditions, are experienced as difficulties to the psychologist’s practice. This professional, still in line with the clinic psychology model, of individualist and isolated attitude, and with biomedicine, of accentuated presence in the cearense context, marked by the vertical, top-to-bottom character of the hierarchy in charge of the assistance, and interested in the other more as an object of technical intervention. Therefore, it is possible to conclude that this model of practice is the prevalent among the psychologists of this study, who, in face of the user, assume the attitude of care as technique, adjustment, control and nullification of the difference. There are, however, experiences that reach beyond the classic clinic attitude and the emphasis on expertise to manage the intersubjective encounter, the dialogue, the sharing of responsibilities, the committment with the social-cultural and political dimension of the health service and, above all, the other, acknowledged and respected as a subject, whom the psychologist needs to approach in order to provide a space of listening to his/her sufferering and appreciation of his/her singularity.